2016
DOI: 10.18632/oncotarget.11011
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TCL6 expression is associated with poor prognosis in patients with clear cell renal cell carcinoma

Abstract: One-third of clear cell renal cell carcinoma (ccRCC) patients present with metastasis at the time of diagnosis. The prognosis of these patients is poor. To identify potential prognostic biomarkers and therapeutic targets for ccRCC, we re-evaluated published long non-coding RNA (lncRNA) expression profiling data from the Gene Expression Omnibus and ArrayExpress database. We found that five lncRNAs were differentially expressed in ccRCC and adjacent tissues. These lncRNAs were assessed in an independent cohort o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
5
41
0
Order By: Relevance
“…Low level of TCL6 was associated with worse overall and disease-free survival of RCC patients. These findings were consistent with a previous study, TCL6 was reported to be negatively correlated with the T, N, M, and TNM stage and serve as an independent predictor via analysis of 71 pairs of RCC samples [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Low level of TCL6 was associated with worse overall and disease-free survival of RCC patients. These findings were consistent with a previous study, TCL6 was reported to be negatively correlated with the T, N, M, and TNM stage and serve as an independent predictor via analysis of 71 pairs of RCC samples [19].…”
Section: Discussionsupporting
confidence: 93%
“…SuperScript II Reverse Transcriptase kit (Invitrogen Life Technologies) was used to generate cDNA. Quantitative real-time PCR analyses were performed according to previous study [19]. Samples were compared using the relative CT method, where the relative expression of TCL6 was normalized to that of GAPDH.…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
“…The three RCC subtype cohorts were further divided into high PD-L1 group and low PD-L1 group based on the median PD-L1 mRNA value (Table 1) [15, 16]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was reported that DLEU2 was involved in several types of cancer and DLEU2 exon 9 was an independent marker of poor prognosis in patients with esophageal adenocarcinoma (31). Aberrant expression levels of TCL6 were involved in clear cell renal carcinoma by regulating the PI3K/AKT pathway and PWRN1 inhibits gastric cancer cell proliferation and metastasis via p53 signaling pathway (32,33).…”
Section: Discussionmentioning
confidence: 99%